Control of tumor progression by angiocrine factors - Alsina Sanchis, Elisenda; Mülfarth, Ronja; Fischer, Andreas (Cancers, 2021)
Tumor progression, therapy resistance and metastasis are profoundly controlled by the tumor microenvironment. The contribution of endothelial cells to tumor progression was initially only attributed to the formation of new blood vessels (angiogenesis). Research in the last decade has revealed however that endothelial cells control their microenvironment through the expression of membrane-bound and secreted factors. Such angiocrine functions are frequently hijacked by cancer cells, which deregulate the signaling pathways controlling the expression of angiocrine factors. Here, we review the crosstalk between cancer cells and endothelial cells and how this contributes to the cancer stem cell phenotype, epithelial to mesenchymal transition, immunosuppression, remodeling of the extracellular matrix and intravasation of cancer cells into the bloodstream. We also address the long-distance crosstalk of a primary tumor with endothelial cells at the pre-metastatic niche and how this contributes to metastasis.
Gesehen am 19.08.2021